A flexible copper sulfide composite membrane with tunable plasmonic resonance absorption for near-infrared light-driven seawater desalination. Issue 2 (16th March 2022) - An, Lu; Wang, Chengbin; Feng, Qunfeng; Xu, Zhenmin; Tian, Qiwei; Chai, Wei; Yang, Shiping; Bian, Zhenfeng
Abstract : A flexible CuS/Matrimid composite membrane with tunable near-infrared absorption is constructed. The composite membrane exhibits good near-infrared light-driven photothermal vapor evaporation and seawater desalination effects. Abstract : Near-infrared light driven devices for water evaporation are strictly limited by their inflexibility, high cost, complicated fabrication processes, and low energy-conversion efficiency. Here, a flexible copper sulfide composite membrane with tunable plasmonic resonance absorption for an efficient near-infrared light photothermal conversion is proposed. Both the uniformity of the morphology and the proportion of Cu + in the flower-like copper sulfide (CuS) superstructure are easily controlled by adjusting the amount of polyvinylpyrrolidone (PVP), which effectively improves the absorption of the CuS superstructure in the near-infrared region. Furthermore, the flexible CuS/Matrimid composite membrane constructed by combining CuS and polyimide membranes exhibits highly flexible properties, strong NIR absorption, fast heating (10 s), and good thermal stability. A highly efficient photothermal conversion is achieved by near-infrared light-driven water evaporation. Under 808 nm light irradiation, the water evaporation conversion efficiency is ca. 80% and has excellent evaporation stability. The flexible CuS/Matrimid composite membrane developed in this study could have promising practical applications in near-infrared light-driven devices for seawater desalination.